Tipe Tuturan Remaja Perempuan Yatim dalam Interaksi Sehari-Hari: Kajian Pragmatik - Ainin, Nur; Rokhmansyah, Alfian; Purwanti (Universitas Mulawarman, 2019)
This study aims to determine the type of speech used by an orphaned teenager in daily communication. This research includes field research in the form of case studies with qualitative approaches and presented descriptively. The main data of the study are speeches in the activities of everyday speech acts. The data source is a 21-year-old orphaned teenager. The results showed that the type of speech used, namely the declarative, representative, expressive, directive, and commissive type. While the dominant sentence form is used, namely direct and literal sentences.